Participação do cálcio citosólico sobre a ação espasmolítica do ácido ent-7a-acetoxitraquiloban-18-óico e de seu derivado hidroxilado em íleo isolado de cobaia - Santos, Rosimeire Ferreira dos (2010)
From the stem bark of Xylopia langsdorfiana A. St.-Hil. & Tul. (Annonaceae), popularly known as pimenteria da terra , was isolated the diterpene ent-7-α-acetoxytrachyloban-18-oic acid (trachylobane-360) from which it was made a structural modification in which the acetoxy group was substituted by hydroxy generating the ent-7a-hidroxitrachyloban-18-oic acid (trachylobane-318). How there are some reports that show spasmolytic activity of some diterpenes, we aimed to investigate this activity on male rat aorta, rat uterus, guinea-pig trachea and ileum. On rat aorta and rat uterus nor trachylobane-360 or its derivative trachylobane-318 promoted significant spasmolytic effect until the concentration of 10-4 M. However on guinea-pig trachea, only the derivative relaxed this organ pre-contracted with carbachol (CCh) in the presence (EC50 = 3.3 0.9 ± 0.4 x 10-5 M) and absence (EC50 = 3.5 ± x 10-5 M) of functional epithelium, in a equipotent manner, suggesting a possible direct effect on tracheal smooth muscle and that the structural modification was essential for the relaxant effect in this organ. On the other hand, on guinea pig ileum, both diterpenes inhibited the phasic contractions induced by CCh or histamine. When the ileum was pre-contracted with KCl, CCh or histamine, the diterpenes induced relaxation and this effect is not by competitive antagonism of histamine, which was confirmed by the shifted of the cumulative curves to histamine to the right, in a non-parallel manner with reduction of the maximal effect (Emax). How the tonic component of contraction induced by KCl, CCh or histamine is maintained mainly by the opening of CaV, we hypothesized that the trachylobanes could be acting on these channels. The hypothesis was confirmed with the observation that both diterpenes antagonized the CaCl2-induced contractions in depolarizing Ca2+-free solution also relaxed the ileum pre-contracted by S-(-) Bay K 8644, an Cav1 agonist (EC50 = 3.5 ± 0.7 x 10-5 e 5.5 ± 0.3 x 10-5 M, respectively) confirming that the Cav subtype involved is the L-type (Cav1.2). To investigate the involvement of K+ channels to the effect of diterpenes as observed that the relaxation curves of trachylobane-360 (EC50 = 0.5 ± 0.04 x 10-4 M) and trachylobane-318 (EC50 = 2.0 ± 0.5 x 10-5 M) were significantly shifted to the right in the presence of 5 mM TEA+, a non-selective channel blocker for K+, suggesting involvement of these channels in the effects of diterpenes. The effect of trachylobane-360 appears to involve the subtypes of K+ channels (KATP, SKCa, Kv and BKCa,) since the CE50 have not changed in the presence of blockers of these channels. Interestingly the effect of trachylobane-318 appears to involve the activation of the channel type KATP, Kv and SKCa but not BKCa, evidenced by shifts from the relaxation curves to the right in the presence of K+ channels blockers as glibenclamide, apamin and 4-AP, respectively. These results all together suggest that the structural change was essential for these differentiated effects, but not for the involvement of the cyclic nucleotides pathway, since that in the presence of aminophylline the relaxation curves of trachylobanes were not modified. Both diterpenes reduce the intensity of fluorescence on intestinal myocytes of guinea-pig ileum stimulated by histamine which reflect reduction of [Ca2+]c, what would explain the spasmolytic effects of these diterpenes in functional level.